ETHNOBOTANICAL STUDY OF AROMATIC AND MEDICINAL PLANTS USED IN TRADITIONAL PHYTOTHERAPY IN MIDELT REGION OF MOROCCO - Zhor Oukadir; Najib Senhaji Rhazi; Said El kinany; Badiaa Lyoussi (Journal of Animal and Plant Sciences, 2024)
The aim of this study is to identify the medicinal virtues of aromatic and medicinal plants (AMPs) used in traditional phytotherapy by the local population, this ethnobotanical study was carried out among the population in the Midelt province (Morocco) based on questionnaires and ethnobotanical surveys conducted during four months of fieldwork from May 2022 to the end of August 2022. The first part concerns the informant and the second concerns the species used in the disease treatment. A total of 100 people, 68 women and 32 men were interviewed and only herbalists and traditional therapists were selected for this study. The ages of population ranged between 20 and more than 60 years, of which illiterate women dominate with a percentage of 50 % and men with a higher level of education dominate with a percentage of 43.75 %. This survey yielded 66 plant species grouped into 30 different families, of which the Lamiaceae genus was the most abundant. Treatments were mostly prepared by decoction with a percentage of 46.17%. Plant species were used absolutely in the treatment of gastrointestinal infections with a percentage of 25.42% followed by respiratory infections (13.13%) using exclusively the by oral administration (58.95%). These promising results constitute a crucial reference for the studied region and for the national medicinal flora and therefore a database to research of new natural substances.
Keywords: Aromatic and medicinal plants; Ethnobotanical surveys; Phytotherapy; Traditional medicine